2023
DOI: 10.3390/sym15071340
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry Perception and Psychedelic Experience

Abstract: This review of symmetry perception has six parts. Psychophysical studies have investigated symmetry perception for over 100 years (part 1). Neuroscientific studies on symmetry perception have accumulated in the last 20 years. Functional MRI and EEG experiments have conclusively shown that regular visual arrangements, such as reflectional symmetry, Glass patterns, and the 17 wallpaper groups all activate the extrastriate visual cortex. This activation generates an event-related potential (ERP) called sustained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 264 publications
(355 reference statements)
0
2
0
Order By: Relevance
“…Global completion, is based on maximum symmetry. In contrast to good continuation, symmetry produces strong responses only in higher-order regions, especially V4 and LOC (e.g., Sasaki et al, 2005 ), symmetry-based grouping was found to require visual awareness ( Devyatko and Kimchi, 2020 ; but see, Makin et al, 2023 ), and the role of symmetry in perceptual organization is not entirely clear because of its interaction with other grouping factors ( van der Helm, 2015 ). For example, a number of researchers argue that grouping by other factors precedes and facilitates grouping by symmetry (see for discussion Machilsen et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Global completion, is based on maximum symmetry. In contrast to good continuation, symmetry produces strong responses only in higher-order regions, especially V4 and LOC (e.g., Sasaki et al, 2005 ), symmetry-based grouping was found to require visual awareness ( Devyatko and Kimchi, 2020 ; but see, Makin et al, 2023 ), and the role of symmetry in perceptual organization is not entirely clear because of its interaction with other grouping factors ( van der Helm, 2015 ). For example, a number of researchers argue that grouping by other factors precedes and facilitates grouping by symmetry (see for discussion Machilsen et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The parametric SPN response was evident in 5 tasks (from 5 different groups of 26 participants) but selectively enhanced in the regularity task (left). Figure from Makin et al (2023).…”
Section: Hosted Filementioning
confidence: 99%
“…Visual symmetry contributes to perceptual organisation and object formation (Bertamini et al, 2018;Makin et al, 2023). Psychophysical research demonstrates that the detection of symmetry is fast and noise tolerant.…”
Section: Introductionmentioning
confidence: 99%
“…Symmetry is also a gestalt grouping principle that aids grouping and figureground segmentation (Koffka, 1935;Wagemans et al, 2012). Many psychophysical studies have investigated symmetry perception in humans (Barlow & Reeves, 1979;Treder, 2010), while the brain response to symmetry has been studied extensively in the last 20 years (for recent reviews see Bertamini et al, 2018;Cattaneo, 2017;Makin et al, 2023). Functional MRI studies have found that visual symmetry activates a network of regions in the extrastriate cortex, centred on object sensitive areas V4 and the Lateral Occipital Complex (Keefe et al, 2018;Kohler et al, 2016;Sasaki et al, 2005;Tyler et al, 2005;Van Meel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%